QUESTIONS OF WORLD AND PERSON IN THE BAHAUDDIN NAQSHBAND’S WORK “AVROD” - Navruzova Gulchehra Nigmatovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes questions of world and person in the work “Avrod” written by the seventh feast of the holy Bukhara, the great Bahauddin Nakshband(1318-1389), known as Shoh Nakshband, Xojai Buzurg, Balogardon, a feast of the 16th ring of the Sufi tariqah of Khojagan Nakshbandiya.